1999
DOI: 10.1080/15216549900201713
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human CR1 gene promoter

Abstract: Abbreviations: CR1, Complement receptor type 1; CR2, complement receptor type 2; DAF, decay accelerating factor; MCP, membrane cofactor protein; C4BR C4 binding protein,; DMSO, Dime@ sulfoxide; MMLV-RTase, Moloney murine lekemia virus reverse transcriptase; HPRT, hypoxanthine phosphoribosyltransferase. SUMMARY:The human CR1 is a single chain membrane glycoprotein that is a member of the group of regulators of the complement activation system. In order to clarify the regulatory mechanisms of human CR1 gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…We had previously shown that the basal human CR1 promoter is located within 376 nucleotides upstream of the transcription initiation site (Kim et al, 1999a) and identified several potential transcription factor-binding sites (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We had previously shown that the basal human CR1 promoter is located within 376 nucleotides upstream of the transcription initiation site (Kim et al, 1999a) and identified several potential transcription factor-binding sites (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The HEL cells were transfected with a reporter construct by electroporation and relative luciferase activities were assayed as described previously (Kim et al, 1999a). Compositions of the plasmids used are described in the figure legend.…”
Section: Transient Transfection and Luciferase Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…They studied a region of ~2kb 5' of the gene, and found no evidence of a typical TATA type promoter sequence, but did find a CAAT-box type sequence (TCAAAA, which had previously been shown to be capable of acting as a CAAT-box (Kunz et al 1989)), which was observed around position -54 to -49. The 5' flanking region was also found to contain a GC-rich region, particularly high in CpG dinucleotides (Kim et al 1999).…”
Section: Cr1 -Genetics and Regulationmentioning
confidence: 99%
“…Due to the different expression levels of CR1, Kim et al (Kim et al 1999) sought to identify the regulatory elements which may control this expression within the promoter of the CR1 gene. They studied a region of ~2kb 5' of the gene, and found no evidence of a typical TATA type promoter sequence, but did find a CAAT-box type sequence (TCAAAA, which had previously been shown to be capable of acting as a CAAT-box (Kunz et al 1989)), which was observed around position -54 to -49.…”
Section: Cr1 -Genetics and Regulationmentioning
confidence: 99%